Congenital tracheo-oesophageal fistula in the adult. - Black, R J (1982)
A case of congenital tracheo-oesophageal fistula without oesophageal atresia in an adult is presented. Surgical repair via a right thoracotomy was successfully undertaken. The 13 previously reported cases in English publications are reviewed.